The development of career planning scale for junior high school students based on cognitive information processing theory - Wang, Peng; Li, Tiantian; Wu, Zhigang; Wang, Xiao; Jing, Jihao; Xin, Jianjun; Sang, Xiuchun; Dai, Binrong (Frontiers in Psychology, 2023)
The purpose of this research was to develop a scale to measure the level of career planning of students taking junior high school information technology course. Based on the career theory of Cognitive Information Processing (CIP), we selected scale items from literature reviews and expert guidance. The scale consisted of 28 items with 4 factors (interests, abilities, values, personality). To test the scale's factor structure, we used confirmatory factor analysis (CFA), and the model was modified according to CFA results. The second-order confirmatory factor analysis was applied to the model of the scale to prove the rationality of the total score. The internal consistency were evaluated using Cronbach's alpha coefficients. In addition, the composite reliability (CR) and average variance extraction (AVE) of the scale were also calculated to test the convergent validity. After related analyses, the scale was proved to have good psychometric properties, which can be used to measure junior high school students’ career planning level in information technology course from the aspects of interest, ability, values, and personality.